2017
DOI: 10.1016/j.jnutbio.2016.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant properties of tea blunt ROS-dependent lipogenesis: beneficial effect on hepatic steatosis in a high fat-high sucrose diet NAFLD obese rat model

Abstract: Oxidative stress could trigger lipid accumulation in liver and thus hepatic steatosis. Tea is able to prevent liver disorders, but a direct link between antioxidant capacities and prevention of steatosis has not been reported yet. We aimed to investigate such relationship in a rat model of high fat-high sucrose diet (HFS)-induced obesity and to explore more deeply the mechanisms in isolated hepatocytes. Wistar rats were divided into a control group (standard diet), an HFS group (high fat-sucrose diet) and an H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 48 publications
(64 reference statements)
3
35
0
Order By: Relevance
“…It has been reported that HFD intervention can lead to a higher oxidative stress in liver, which contributes to hepatic lipid accumulation and thereby results in many other diseases in liver . Therefore, regulation of hepatic oxidative stress by antiobesogenic candidates is considered to have an important role in alleviation of obesity .…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that HFD intervention can lead to a higher oxidative stress in liver, which contributes to hepatic lipid accumulation and thereby results in many other diseases in liver . Therefore, regulation of hepatic oxidative stress by antiobesogenic candidates is considered to have an important role in alleviation of obesity .…”
Section: Resultsmentioning
confidence: 99%
“…The development of hepatic steatosis is associated with altered mitochondrial morphology [ 18 ]. Ultrastructural changes of the mitochondria were further revealed by a transmission electron microscopy assay, and are shown in Figure 4 .…”
Section: Resultsmentioning
confidence: 99%
“…It has previously been reported that ROS overproduction promotes neutral lipid accumulation in hepatocytes, thus contributing to the development of NAFLD (Ferramosca et al, 2017;Braud et al, 2017). To determine whether Cori alleviated PA/OA-induced intracellular fat accumulation through suppressing intracellular ROS levels, we next measured the intracellular ROS levels by using DCFH-DA, a peroxide/redoxsensitive fluorescent probe.…”
Section: Cori Suppressed Intracellular Pa/oa Induced Ros Levelsmentioning
confidence: 99%